2008
DOI: 10.3844/ajavsp.2008.36.39
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Mastitis Pathogens and their Resistance Against Antimicrobial Agents in Dairy Cows in Jordan

Abstract: The primary objective of this study was to determine the aetiology of bovine mastitis in ten herds of Holstein Friesian cow in Jordan, the prevalence of mastitis pathogens in dairy cows and their resistance to selected antimicrobial agents. Milk samples were collected from 220 lactating cows to determine the clinical and subclinical mastitis by white side test and confirmed by cultural tests. It was found that 138 quarters 15.7% had been diagnosed as clinical mastitis with definite gross pathological lesions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
(16 reference statements)
5
27
1
1
Order By: Relevance
“…This finding runs counter to those of other studies that have been conducted nationally and internationally. Studies that have targeted the prevalence rate of contagious mastitis in Jordan showed a higher prevalence rate (35-45%) (Lafi et al 1994;Hawari and Al-Dabbas 2008;Al-Tarazi et al 2011), whereas in other parts of the world a lower rate was reported (0.5-14%) (De Vliegher et al 2012). The reasons for this discrepancy may lie in the warmer weather in Jordan as well as the lack of implementation of hygiene control measures, fly control, optimal nutrition, inter-sucking among young stock in addition to the comfort measures, especially around calving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding runs counter to those of other studies that have been conducted nationally and internationally. Studies that have targeted the prevalence rate of contagious mastitis in Jordan showed a higher prevalence rate (35-45%) (Lafi et al 1994;Hawari and Al-Dabbas 2008;Al-Tarazi et al 2011), whereas in other parts of the world a lower rate was reported (0.5-14%) (De Vliegher et al 2012). The reasons for this discrepancy may lie in the warmer weather in Jordan as well as the lack of implementation of hygiene control measures, fly control, optimal nutrition, inter-sucking among young stock in addition to the comfort measures, especially around calving.…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, several studies have been conducted in order to investigate bovine mastitis (Lafi et al 1994;Lafi and Hailat 1998a;Lafi and Hailat 1998b;Hawari and Al-Dabbas 2008), but only one study focused on mastitis in heifers (Al-Tarazi et al 2011). In Jordan, research aimed at improving control measures for infectious diseases, especially mastitis, is still in its infancy at best.…”
mentioning
confidence: 99%
“…Nigella (Nigella sativa L.) is an annual herbaceous plant belonging to the Ranunculaceae family growing in countries bordering the Mediterranean Sea and is cultivated throughout India and other tropical regions of the world (Mehta et al, 2008;Saganuwan, 2009;Cheikh-Rouhou et al, 2007). A number of reports have been published on the action of N. sativa extracts or its oil on the different bacterial isolated (Al-Haj et al, 2010;Hawari and Al-Dabbas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus is one of the most common causes of contagious bovine mastitis and subclinical mastitis in dairy cattle worldwide and 50-100% of herds may be infected with this pathogen (Radostits et al, 2000;Morgan, 2008) The seed of Nigella sativa Linn. (Ranunculaceae), commonly known as black seed or black cumin, is used in herbal medicine all over the world for the treatment and prevention of a number of diseases and conditions that include asthma, diarrhoea and dyslipidaemia (Hawari and Al-Dabbas, 2008). Nigella (Nigella sativa L.) is an annual herbaceous plant belonging to the Ranunculaceae family growing in countries bordering the Mediterranean Sea and is cultivated throughout India and other tropical regions of the world (Mehta et al, 2008;Saganuwan, 2009;Cheikh-Rouhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…E on the 21 st and 12 th day before calving in D1 group had an impact on reducing acute clinical mastitis forms. Hawari and Al-Dabbas (2008) point to the various forms of mastitis and bacterial agents isolated from the udders for cows in 10 farms of Holstein Friesian cattle in Jordan. Up to 15.7% reported cases of clini-cal mastitis with macroscopic changes of the mammary gland and with excretions or secretions were reported.…”
Section: Discussionmentioning
confidence: 99%